PROPERTIES OF NEW SALTS OF 2-(5-(ADAMANTANE-1-YL)-4-R-1,2,4-TRIAZOLE-3-YLTIO)ACETIC ACIDS IN THE GLUCOSE TOLERANCE TEST - V. M. Odyntsova; Ye. S. Pruhlo; O. I. Panasenko; Ye. H. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
The concentration of glucose in the blood is one of the integral indicators of the internal environment that reflects the metabolism of carbohydrates, proteins and fats in the body. Glucose is a key component of human metabolism. The level of blood sugar is one of the most important controlled constants of body that defines homeostasis and displays the status of carbohydrate metabolism. Low blood sugar (hypoglycemia) is a dangerous condition when blood glucose is critically low.